Written in blood: fatal attraction in enlightenment Amsterdam - Spierenburg, Pieter (History of crime and criminal justice series, 2004)
A big city in cultural flux : eighteenth-century Amsterdam -- No one suspected he would end as a murderer -- A new woman -- How to dump a body when there are no cars? -- Nathaniel's acension -- An unsuccessful career -- An infamous infatuation -- Honor, shame, and notoriety -- Van Gogh's last blood.